Pengaruh Metode Struktural Analitik Sintetik Terhadap Kemampuan Menulis Permulaan Siswa Fase A SDN 09 Kota Bengkulu - Aisyi, Nadilla Rihadatul; Gumono; Amaliyah, Yuli (JURIDIKDAS, 2025)
This research investigates the influence of the Structural Analytic Synthetic (SAS) method on the initial writing skills of Phase A students at SDN 09 Kota Bengkulu. Employing a quantitative approach with a Matching Only Pretest-Posttest Control Group Design, the study involved all second-grade students at SDN 09, specifically classes IIA, IIB, and IIC. Using cluster random sampling, 24 students from class II A were designated as the experimental group, while 26 students from class II B formed the control group. Data collection was conducted using a beginning writing assessment consisting of five items. The descriptive analysis revealed that the experimental group's average posttest score was 76.04, whereas the control group scored 66.35. An independent sample t-test showed a t-count of 3.251, which exceeded the t-table value of 1.677, with a significance level (2-tailed) of 0.002, indicating a statistically significant difference between the two groups. These findings suggest that the SAS method has a meaningful impact on improving early writing abilities among Phase A students at SDN 09 Kota Bengkulu.